The relationship of neutrophil-to-lymphocyte ratio with health-related quality of life, depression, and disease activity in SLE: a cross-sectional study - Papachristodoulou, Eleni; Kakoullis, Loukas; Christophi, Costas A.; Psarelis, Savvas; Hajiroussos, Victor; Parperis, Konstantinos (My University, 2023)
The neutrophil-to-lymphocyte ratio (NLR) emerged as a potential biomarker in SLE, but its association with several outcomes remains unclear. We aimed to evaluate the relationship between NLR and SLE disease activity, damage, depression, and health-related quality of life. A cross-sectional study was conducted, including 134 patients with SLE who visited the Division of Rheumatology between November 2019 and June 2021. Demographics and clinical data including NLR, Safety of Estrogens in Lupus Erythematosus National Assessment-Systemic Lupus disease activity index (SELENA-SLEDAI), Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI), physician global assessment (PhGA), patient global assessment (PGA), patient health questionnaire (PHQ)-9, patient self-rated health, and lupus quality of life (LupusQoL) scores, were collected. Patients were stratified into two groups and compared using the NLR cut-off of 2.73, the 90th percentile value of healthy individuals. The analysis included t-test for continuous variables, χ2-test for categorical variables, and logistic regression adjusting for age, sex, BMI, and glucocorticoid use. Among the 134 SLE patients, 47 (35%) had an NLR ≥ 2.73. The NLR ≥ 2.73 group had significantly higher rates of severe depression (PHQ ≥ 15), poor/fair self-rated health, and the presence of damage (SDI ≥ 1). These patients also scored significantly lower in LupusQoL domains (physical health, planning, and body image), and higher in SELENA-SLEDAI, PhGA, and PGA. Logistic regression confirmed that high NLR is associated with severe depression (PHQ ≥ 15) (OR:7.23, 2.03-25.74), poor/fair self-rated health (OR:2.77,1.29-5.96), high SELENA-SLEDAI score(≥ 4) (OR:2.22,1.03-4.78), high PhGA (≥ 2) (OR:3.76, 1.56-9.05), and presence of damage (SDI ≥ 1) (OR:2.67, 1.11-6.43). High NLR in SLE may indicate depression, worse quality of life, active disease, and the presence of damage.
Keywords: Biomarker; Depression; Quality of life; Systemic lupus erythematosus